Produção, Tratamento e Uso dos Dejetos Suínos no Brasil - Bárbara Françoise Cardoso (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2015)
The aim of this article is to describe the main environmental problems that can be caused by swine waste and the main forms of handling of swine waste, highlighting the most used in Brazil. The methodology based on the bibliographic research, in which publications, books and monographs, as well as specialized sites were used. This research showed that the contamination of the ground water is the most important environmental problem caused by the inappropriate handling of swine waste and that there are six main types of swine waste handling processes used in Brazil: settling ponds, manure storage tanks, bi- manure storage tanks, bio-digesters, composting and deep bedding. All these types of handling seeking to minimize environmental impacts caused by the swine waste, having no order of importance among them, since the choice of the process is given by the amount of waste produced mainly. In Brazil, the use of manure storage tanks and settling ponds prevails, however among the properties integrated to large food companies there is the use of bio-digesters. The composting and the deep bedding are alternatives less used because they were implemented in Brazil recently.